2010
DOI: 10.1080/02791072.2010.10399783
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Psychiatric Symptomatology in Adolescents Attending a Community Drug and Alcohol Treatment Program

Abstract: This study examines mental health symptoms in a cohort of adolescents with substance use disorder (SUD), and attempts to determine if mental health symptoms differed by gender. We retrospectively looked at the Beck's Youth Inventory Second Edition (BYI-II) scores of 88 clients attending a community drug and alcohol treatment service in Dublin, Ireland that were completed at intake as part of their assessment. The raw and T-scores of the male patients were compared against their female counterparts and both aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…While most studies show males in the general population are more likely to externalize (Darves-Bornoz et al 1998; Gallerani et al 2010), a national probability study on victims of child maltreatment show female adolescents are more likely to externalize than male adolescents (Wall et al 2005). A study on gender differences in psychiatric symptoms among adolescents by Edokpolo et al (2010) found that females with substance use disorders had more externalizing and internalizing problems than males. In this research, female adolescents appeared to be at higher risk than males for co-occurring ID and ED problems and ID-only problems.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies show males in the general population are more likely to externalize (Darves-Bornoz et al 1998; Gallerani et al 2010), a national probability study on victims of child maltreatment show female adolescents are more likely to externalize than male adolescents (Wall et al 2005). A study on gender differences in psychiatric symptoms among adolescents by Edokpolo et al (2010) found that females with substance use disorders had more externalizing and internalizing problems than males. In this research, female adolescents appeared to be at higher risk than males for co-occurring ID and ED problems and ID-only problems.…”
Section: Discussionmentioning
confidence: 99%
“…Following a long gap in research activity, several recent studies conducted in substance abuse services have confirmed differences between young males and females in the prevalence of cooccurring emotional and behavioural health problems (Dean, McBride, MacDonald, Connolly, & McDermott, 2010;Edokpolo, James, Kearns, Campbell, & Smyth, 2010;Hodgins, Lovenhag, Rehn, & Nilsson, 2014;James, Smyth, & Apantaku-Olajide, 2012;Keane, Ducray, & Smyth, 2015;Slesnick & Prestopnik, 2005;Wu, Lu, Sterling, & Weisner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, young women usually present to substance use services with more severe substance abuse and psychosocial problems in general. [28][29][30] Because males make up most of the new referrals into the service, one might expect the service to have adopted practices that are more focused around the engagement of boys. Despite this, we found better engagement and retention in females, perhaps because the girls presenting to "Altered High" have more severe problems.…”
Section: Discussionmentioning
confidence: 99%